A Portrait Of Educational Reform In Ibn Ashur's Tafsir - Zamakhsyari bin Hasballah Thaib; Mukhamad Hadi Musollin; Vina Annisa (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2026)
This article aims to describe the views of Muhammad al-Thahir Ibn Ashûr regarding educational reform and improvement through his interpretation of Qur’anic verses in his exegetical work al-Tahrir wa al-Tanwir. This study is a library-based research employing a descriptive-analytical method, in which the author outlines various perspectives of Ibn Ashûr on educational reform derived from his interpretation of verses related to the educational objectives (maqāṣid) in the Qur’an. Among the findings of this research is that Ibn Ashûr not only implemented educational reforms during his tenure as Sheikh of al-Zaytuna University on a practical level, but also laid important theoretical foundations concerning the principles, means, and priorities of reform and improvement in the field of education through his Qur’anic interpretation. His approach is notably centered on the maqāṣid of the Qur’an as guidance for humanity.